Route Report - 081, 7 May 1926
1926-05-07 1918-1939 "Route Report - 081, 7 May 1926" [g0408001.jpg], 7 May 1926, Trades Union Congress Report from a Despatch rider travelling from London through Dartford, Chatham and Canterbury to Dover all postal services were disrupted and very few local union or trades council officers had telephones in 1926, a communications network using despatch riders was established.